MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN HASIL BELAJAR SISWA PADA MUATAN IPA MENGGUNAKAN MODEL SENTER DI SEKOLAH DASAR - Aulianti, Amanda Irgi; Sari, Raihanah; Fathul Jannah; Akhmad Riandy Agusta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The problem in this research is the low level of critical thinking skills, and student learning outcomes regarding hot content and material and the transfer of science learning content. This is caused by lack of critical thinking training, poor memory, and students' ability to understand the concepts being taught. The SENTER model, which is a combination of Problem Based Learning, Student Centered Learning, and Numbered Head Together, is designed to critical thinking, and student learning outcomes. The purpose of this research is to analyze critical thinking skills and student learning outcomes.This research used a type of Classroom Action Research (PTK), which was carried out over four meetings. Class V students of SDN Kuin Selatan 1 Banjarmasin for the 2022/2023 academic year, consisting of 17 students, are the subjects of this research. Data collection methods use tests and observations. This research collects qualitative and quantitative data. Data analysis was carried out using descriptive techniques such as tables, graphs and percentage interpretation.The results showed that students' critical thinking skills increased by 88% and student learning outcomes increased by 92% for the